Building AI driven marketing capabilities understand customer needs and deliver value through AI - Zaidi, Neha; Maurya, Mohit; Grima, Simon; Tyagi, Pallavi (Apress, 2024)
This book provides insight into technologies that offer competitive advantage in marketing. These technologies can help us with describing and predicting customer behavior with the help of analytics, designing of radical products, creating of meaningful value, optimization of distribution, informing and promoting solutions, and making marketing more effective overall by aligning marketing with business goals. A range of technologies, such as analytics, big data, artificial intelligence, IoT, machine learning are expected to transform future businesses. Understanding customer needs, matching them to solutions and delivering value can all be dramatically optimized with the help of technology. Businesses need to realize that AI has already made inroads in marketing and can be expected to wield its influence across functional areas in the foreseeable future. The business world is headed towards acceptance of technology to synthesize knowledge by interpreting diverse information and facilitating decision making. This book is an attempt to reflect deployment of technologies across businesses and sectors. As the functional discipline comes together, harnessing a gamut of technologies becomes indispensable to deliver a superior customer experience and driving profits. Marketers should thus adopt the concepts of openness, convergence, and creation of value through new emerging technologies. A resultant hyper connected market will thus have to adopt innovative changes in its existing processes and services. The proposed book offers its readers an insight into technological interventions in various aspects of marketing domain. From understanding various technologies as an enabler to marketing efforts and its impact on decision making and mapping of various facets of customer experience, this book is recommended for marketers and learners to understand the advantages of using technology.
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on February 19, 2024)
Keywords: Marketing -- Technological innovations; Artificial intelligence; Marketing; Innovations; Intelligence artificielle; artificial intelligence